A Review on the Progress and Future of TiO2/Graphene Photocatalysts - Nasir, Amara; Khalid, Sadia; Yasin, Tariq; Mazare, Anca Valentina (Energies, 2022)
TiO2 is seen as a low cost, well-known photocatalyst; nevertheless, its sluggish charge kinetics does limit its applications. To overcome this aspect, one of the recent approaches is the use of its composites with graphene to enhance its photoactivity. Graphene-based materials (nanosheets, quantum dots, etc.) allow for attachment with TiO2 nanostructures, resulting in synergistic properties and thus increasing the functionality of the resulting composite. The current review aims to present the marked progress recently achieved in the use of TiO2/graphene composites in the field of photocatalysis. In this respect, we highlight the progress and insights in TiO2 and graphene composites in photocatalysis, including the basic mechanism of photocatalysis, the possible design strategies of the composites and an overview of how to characterize the graphene in the mixed composites. The use of composites in photocatalysis has also been reviewed, in which the recent literature has opened up more questions related to the reliability, potential, repeatability and connection of photocatalytic mechanisms with the resulting composites. TiO2/graphene-based composites can be a green light in the future of photocatalysis, targeting pollution remediation, energy generation, etc.
CRIS-Team WoS Importer:2022-09-16